Assessing the Photoinduced Electron-Donating Behavior of Carbon Nanodots in Nanoconjugates - Ferrer-Ruiz, Andres; Scharl, Tobias; Rodriguez-Perez, Laura; Cadranel, Alejandro; Angeles Herranz, M.; Martin, Nazario; Guldi, Dirk Michael (Journal of the American Chemical Society, 2020)
Carbon nanodots (CNDs) undergo electron transfer in different scenarios. Previous studies have mainly focused on the electron-accepting features of CNDs in covalently linked donor-acceptor nanoconjugates. In view of this, we decided to carry out in this study the formation of covalently linked nanoconjugates that feature electron-donating pressure synthesized carbon nanodots (pCNDs) and electron-accepting 11,11,12,12-tetracyano-9,10-anthra-p-quinodimethane (TCAQ): pCND-TCAQ The stability of the one-electron reduced form of TCAQ renders it the acceptor of choice. Detailed structural and electrochemical investigations allowed the characterization of pCND-TCAQ Furthermore, investigations regarding intramolecular interactions, by means of steady-state and pump-probe transient absorption spectroscopies, allowed detection and characterization of three excited state species, in general, and the pCND(center dot+)-TCAQ(center dot-) charge-separated state, in particular.
CRIS-Team WoS Importer:2021-02-05

Carbon Nanodots for All-in-One Photocatalytic Hydrogen Generation - Jana, Bikash; Reva, Yana; Scharl, Tobias; Strauss, Volker; Cadranel, Alejandro; Guldi, Dirk Michael (Journal of the American Chemical Society, 2021)
Carbon nanodots (CNDs) were photochemically altered to produce dihydrogen under light irradiation. Within the complex structure of CNDs, photo-oxidation takes place at citrazinic acid molecular fluorophore sites. Important is the fact that the resulting CND materials have a dual function. On one hand, they absorb light, and on the other hand, they photo- and electrocatalytically produce dihydrogen from water and seawater, without any external photosensitizer or cocatalyst. Record HER activities of 15.15 and 19.70 mmol(H2) g(catalyst)-1 h-1 were obtained after 1 h of 75 mW/cm2 Xe lamp illumination, from water and seawater, respectively. This impressive performance outweighs the remaining structural uncertainties. A full-fledged physicochemical investigation based on an arsenal of steady-state and time-resolved spectroscopic characterizations together with microscopy enabled a comprehensive look into the reaction mechanism. For an efficient dihydrogen formation, a precatalytic activation by means of reduction with a sacrificial electron donor is imperative.
CRIS-Team Scopus Importer:2021-12-24

Charge transfer in graphene quantum dots coupled with tetrathiafulvalenes - Scharl, Tobias; Ferrer-Ruiz, Andres; Saura-Sanmartin, Adrian; Rodriguez-Perez, Laura; Angeles Herranz, M.; Martin, Nazario; Guldi, Dirk Michael (Chemical Communications, 2019)
Water-soluble fluorescent graphene quantum dots have been successfully prepared through a top-down approach, that is, starting with graphite, and covalently functionalizing it with π-extended tetrathiafulvalene. Charge transfer investigations reveal noticeably slower charge recombination when compared with exTTF nanoconjugates featuring carbon nanodots, for which a larger presence of trap states is observed.
CRIS-Team Scopus Importer:2019-06-07

Exploring Tetrathiafulvalene–Carbon Nanodot Conjugates in Charge Transfer Reactions - Ferrer-Ruiz, Andres; Scharl, Tobias; Haines, Philipp; Rodriguez-Perez, Laura; Cadranel, Alejandro; Herranz, M. Angeles; Guldi, Dirk Michael; Martin, Nazario (Angewandte Chemie International Edition, 2018)
Carbon nanodots (CNDs) were synthesized using low-cost and biocompatible starting materials such as citric acid/urea, under microwave irradiation, and constant pressure conditions. The obtained pressure-synthesized CNDs (pCNDs) were covalently modified with photo- and electroactive π-extended tetrathiafulvalene (exTTF) by means of a two-step esterification reaction, affording pCND-exTTF. The electronic interactions between the pCNDs and exTTF were investigated in the ground and excited states. Ultrafast pump–probe experiments assisted in corroborating that charge separation governs the deactivation of photoexcited pCND-exTTF. These size-regular structures, as revealed by AFM, are stable electron donor–acceptor conjugates of interest for a better understanding of basic processes such as artificial photosynthesis, catalysis, and photovoltaics, involving readily available fluorescent nanodots.
CRIS-Team Scopus Importer:2022-04-14
Keywords: carbon nanodots; charge transfer; donor–acceptor systems; excited state dynamics; tetrathiafulvalene

Fine-tuning the assemblies of carbon nanodots and porphyrins - Scharl, Tobias; Cadranel, Alejandro; Haines, Philipp; Strauß, Volker; Bernhardt, Sarah; Vela, Sonia; Atienza, Carmen; Gröhn, Franziska; Martin, Nazario; Guldi, Dirk Michael (Chemical Communications, 2018)
We present charge-transfer assemblies of electron accepting, pressure-synthesized carbon nanodots (pCNDs) and an electron donating porphyrin. Amidine derivatization of the porphyrin allows for hydrogen bonding interactions with the carboxyl groups on the surface of pCNDs, which drive the formation of the assembly. Upon photoexcitation, this electron donor-acceptor supramolecular construct features ultrafast charge separation, and subsequent charge recombination in 27 ps.
CRIS-Team Scopus Importer:2022-04-14

Improving charge injection and charge transport in CuO-based p-type DSSCs-a quick and simple precipitation method for small CuO nanoparticles - Langmar, Oliver; Ganivet, Carolina R.; Schol, Peter; Scharl, Tobias; De La Torre, Gema; Torres, Tomas; Costa Riquelme, Rubén Dario; Guldi, Dirk Michael (Journal of Materials Chemistry C, 2018)
Herein, we introduce a co-precipitation synthesis of CuO, which produces small and uniform nanoparticles (∼12 nm) with a specific surface area of 97.3 m2 g-1. The resulting CuO nanoparticles are superior to the commercial ones, which have previously been used to prepare p-type DSSCs. In turn, we compared p-type DSSCs consisting of CuO-based photocathodes based on newly synthesized and commercial nanoparticles. Devices based on new CuO nanoparticles enable higher dye loadings, and, in turn, superior short-circuit current densities and efficiencies. To corroborate our findings, electrochemical impedance spectroscopy and intensity modulated photocurrent spectroscopy assays were conducted, revealing a better charge injection and faster charge transport for those photocathodes featuring the new CuO nanoparticles.
CRIS-Team Scopus Importer:2022-04-14

Intrinsic and Extrinsic Incorporation of Indium and Single-Walled Carbon Nanotubes for Improved ZnO-Based DSSCs - Schol, Peter; Zhang, Wen Shan; Scharl, Tobias; Kunzmann, Andreas; Peukert, Wolfgang; Schröder, Rasmus R.; Guldi, Dirk Michael (Advanced Energy Materials, 2022)
A common goal in renewable energy research is the production of semiconductor layers with matching additives to gain desirable effects and advantages. Important examples are adjustment of the band gap, enhancing the conductivity, tailoring roughness of the semiconductor, or reducing the recombination rate of charge carriers. In this work a twofold approach is demonstrated. First, the intrinsic incorporation of indium into zinc oxide tunes the band gap of the semiconductor layer of the DSSCs. Second, single-walled carbon nanotubes (SWCNT) as an extrinsic additive improves the charge transport capabilities. To better combine the SWCNTs with the semiconductor layer a protective ZnO shell is grown on the SWCNTs. A combination of current–voltage, incident photon to current efficiency, and electrochemical impedance spectroscopic assays corroborates the positive effects of both additives on the cell performance. The effective charge-carrier diffusion lengths are enhanced from 0.52 µm for pure ZnO to 5.12 µm for low SWCNT concentrations and 15 mol% of indium. This, as well as the increase in collection efficiency from 30.3% to 62.3% enables enhanced transport in these novel devices. A final device utilizing 0.1 wt% SWCNT@ZnO20nm and In15Zn85O yields a current density of 16.49 mA cm−2 and an efficiency of 4.46%.
CRIS-Team Scopus Importer:2022-03-11
Keywords: indium–zinc oxide photoanodes; n-type DSSCs; semiconductor doping; single-wall carbon nanotubes

Modifying the Semiconductor/Electrolyte Interface in CuO p-Type Dye-Sensitized Solar Cells: Optimization of Iodide/Triiodide-Based Electrolytes - Langmar, Oliver; Ganivet, Carolina R.; Scharl, Tobias; De La Torre, Gema; Torres, Tomas; Costa, Ruben Dario; Guldi, Dirk Michael (ACS Applied Energy Materials, 2018)
Studies related to novel electrolyte concepts for p-type dye-sensitized solar cells (p-DSSCs) set focus on developing alternatives to the iodide/triiodide (I-/I-3(-)) redox couples, while attempts to improve the performance of the latter are scarce. In this study, we report on the first complete optimization of an I-/I-3(-)-based electrolyte for p-DSSCs employing CuO-based photocathodes. Optimization of the electrolyte solvent, the effect of ionic liquids, and the concentration-dependent properties of various electrolyte additives were at the focal point. Electrochemical impedance spectroscopy and intensity-modulated photovoltage and photocurrent spectroscopies complemented basic electrochemical and device characterization, leading to a sound understanding of charge injection, charge recombination, and charge transport. To this end, optimization of the aforementioned parameters enabled 2-fold device efficiencies of 0.156% compared to 0.078% for nonoptimized devices.
CRIS-Team WoS Importer:2019-03-01

Noncovalent Liquid Phase Functionalization of 2H-WS2with PDI: An Energy Conversion Platform with Long-Lived Charge Separation - Scharl, Tobias; Binder, Gerhard; Chen, Xin; Yokosawa, Tadahiro; Cadranel, Alejandro; Knirsch, Kathrin; Spiecker, Erdmann; Hirsch, Andreas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2022)
Transition metal dichalcogenides are attractive 2D materials in the context of solar energy conversion. Previous investigations have focused predominantly on the properties of these systems. The realization of noncovalent hybrids with, for example, complementary electroactive materials remains underexplored to this date for exfoliated WS2. In this contribution, we explore WS2 by means of exfoliation and integration together with visible light-absorbing and electron-accepting perylene diimides into versatile electron-donor acceptor hybrids. Important is the distinct electron-donating feature of WS2. Detailed spectroscopic investigations of WS2-PDI confirm the electron donor/acceptor nature of the hybrid and indicate that green light photoexcitation leads to the formation of long-lived WS2+-PDIcharge-separated states.
CRIS-Team Scopus Importer:2022-04-14

Ping-Pong Energy Transfer in Covalently Linked Porphyrin-MoS2 Architectures - Canton-Vitoria, Ruben; Scharl, Tobias; Stergiou, Anastasios; Cadranel, Alejandro; Arenal, Raul; Guldi, Dirk Michael; Tagmatarchis, Nikos (Angewandte Chemie International Edition, 2020)
Molybdenum disulfide nanosheets covalently modified with porphyrin were prepared and fully characterized. Neither the porphyrin absorption nor its fluorescence was notably affected by covalent linkage to MoS2. The use of transient absorption spectroscopy showed that a complex ping-pong energy-transfer mechanism, namely from the porphyrin to MoS2 and back to the porphyrin, operated. This study reveals the potential of transition-metal dichalcogenides in photosensitization processes.
CRIS-Team WoS Importer:2020-02-07

Symmetry-Breaking Charge-Transfer Chromophore Interactions Supported by Carbon Nanodots - Cacioppo, Michele; Scharl, Tobias; Dordevic, Luka; Cadranel, Alejandro; Arcudi, Francesca; Guldi, Dirk Michael; Prato, Maurizio (Angewandte Chemie International Edition, 2020)
Carbon dots (CDs) and their derivatives are useful platforms for studying electron-donor/acceptor interactions and dynamics therein. Herein, we couple amorphous CDs with phthalocyanines (Pcs) that act as electron donors with a large extended pi-surface and intense absorption across the visible range of the solar spectrum. Investigations of the intercomponent interactions by means of steady-state and pump-probe transient absorption spectroscopy reveal symmetry-breaking charge transfer/separation and recombination dynamics within pairs of phthalocyanines. The CDs facilitate the electronic interactions between the phthalocyanines. Thus, our findings suggest that CDs could be used to support electronic couplings in multichromophoric systems and further increase their applicability in organic electronics, photonics, and artificial photosynthesis.
CRIS-Team WoS Importer:2020-05-29

Synthesis and excited state processes of arrays containing amine-rich carbon dots and unsymmetrical rylene diimides - Đorđević, Luka; Haines, Philipp; Cacioppo, Michele; Arcudi, Francesca; Scharl, Tobias; Cadranel, Alejandro; Guldi, Dirk Michael; Prato, Maurizio (Materials Chemistry Frontiers, 2020)
Combining carbon dots (CDs) with π-extended chromophores is an attractive way to study the electronic and energy processes of the former as a key step to many applications, including photosensing, photocatalysis, or photosensitization. CDs, in conjugation with chromophores, can have value in preparing donor-acceptor hybrids, and can also be used as scaffolds to support electronic communication between dyes. In this work, we conjugate two different rylene diimides, naphthalene and perylene diimides (NDI and PDI, respectively), with amorphous nitrogen-doped carbon dots. We take advantage of the imidization reaction between the amine-rich surface of the carbon dots and the monimide monoanhydride precursors of NDIs and PDIs, under microwave assisted conditions. The resulting (nano)hybrids were characterized also by spectroscopic methods. In particular, time-resolved spectroscopy for the multichromophoric array, consisting of CDs and both rylene diimides, allowed us to elucidate the complex inter-chromophoric interactions taking place in the excited state.
CRIS-Team Scopus Importer:2020-12-11

Understanding the Visible Absorption of Electron Accepting and Donating CNDs - Reva, Yana; Jana, Bikash; Langford, Daniel; Kinzelmann, Marina; Bo, Yifan; Schol, Peter; Scharl, Tobias; Zhao, Xinyi; Crisp, Ryan; Drewello, Thomas; Clark, Timothy; Cadranel, Alejandro; et al. (Small, 2023)
Carbon nanodots (CNDs) synthesized from citric acid and formyl derivatives, that is, formamide, urea, or N-methylformamide, stand out through their broad-range visible-light absorbance and extraordinary photostability. Despite their potential, their use has thus far been limited to imaging research. This work has now investigated the link between CNDs’ photochemical properties and their chemical structure. Electron-rich, yellow carbon nanodots (yCNDs) are obtained with in situ addition of NaOH during the synthesis, whereas otherwise electron-poor, red carbon nanodots (rCNDs) are obtained. These properties originate from the reduced and oxidized dimer of citrazinic acid within the matrix of yCNDs and rCNDs, respectively. Remarkably, yCNDs deposited on TiO2 give a 30% higher photocurrent density of 0.7 mA cm−2 at +0.3 V versus Ag/AgCl under Xe-lamp irradiation (450 nm long-pass filter, 100 mW cm−2) than rCNDs. The difference in overall photoelectric performance is due to fundamentally different charge-transfer mechanisms. These depend on either the electron-accepting or the electron-donating nature of the CNDs, as is evident from photoelectrochemical tests with TiO2 and NiO and time-resolved spectroscopic measurements.
Created from Fastlane, Scopus look-up
Keywords: carbon nanodots; excited state; photoelectrochemistry; semiconductors; time-resolved spectroscopy